Glyphosate Use in Agriculture and Birth Outcomes of Surrounding Populations - Mateus Dias; Rudi Rocha; Rodrigo R. Soares (Institute of Labor Economics (IZA), 2019)
This paper assesses the impact of glyphosate use in agriculture on birth outcomes of human populations in surrounding areas. Glyphosate is the most widely used herbicide in the world. Still, despite ongoing controversy, little is known about its effects on human populations at large. Our empirical strategy relies on the fact that glyphosate is strongly complementary to the use of genetically modified seeds in soybean production. We use an instrument based on the gains in productivity from adoption of genetically modified soybeans and look at externalities across municipalities sharing the same water resources. We detect negative and statistically significant effects of glyphosate use on birth outcomes. Our results indicate externality effects of glyphosate use on populations distant from the original locations of use, but receiving water from these locations.
Keywords: I18; Q53; Q15; O33; 330; glyphosate; herbicides; birth outcomes; infant mortality; water; externalities